Vietnamese EFL Students’ Perceptions of Difficulties in Achieving English Oral Communicative Competence (International Journal of Scientific Research and Management (IJSRM), 2023)
In response to the reform in education proposed by the Ministry of Education and Training (MoET) of Vietnam, the pendulum of most teaching and learning activities has swung their concentration to communicative competence-based approaches. Developing communicative competence amongst students of English has received tons of effort from related stakeholders such as teachers, students, educators, researchers and policy makers. The number of studies investigating this shift to date, however, has remained scared. The current study, therefore, aims to investigate the perception of English as a Foreign Language (EFL) students about the difficulties they encounter in achieving English oral communicative competence. Sixty-five students volunteered to participate in the study. The study employed a questionnaire as an instrument for data collection. The results show that the students underwent a certain number of difficulties related to linguistic, sociocultural, discourse, formulaic, interactional and strategic knowledge in the process of achieving oral communicative competence.